Health equity during COVID-19: A qualitative study on the consequences of the syndemic on refugees' and asylum seekers' health in reception centres in Bologna (Italy) - Delia Da Mosto; Chiara Bodini; Leonardo Mammana; Giulia Gherardi; Mattia Quargnolo; Maria Pia Fantini (Elsevier, 2021)
Background: As coronavirus infection spread across the world, the dramatic consequences of Sars-CoV-2 and confinement measures highlighted the disparities within our society, impacting more severely on the wellbeing of the most disadvantaged groups of people, such as migrants. The structural characteristics of reception centres create many challenges in the implementation of measures to contrast the diffusion of the virus, putting refugees and asylum seekers (RAS) even more at risk. For these reasons, we carried out a qualitative study to analyze the impact of the syndemic on the health of RAS who reside in reception facilities in Bologna (one of the cities with the highest number of migrants in Italy) and the measures that were introduced to contrast the diffusion of Sars-CoV-2. Methods: Between April and September 2020, we interviewed 25 professionals and volunteers who were critical in the management of the COVID-19 epidemic in reception centres. Key-informants were selected through a snowball sampling process and covered various professions (i.e. doctors, nurses, social workers, psychologists, cultural mediators, anthropologists, lawyers). The semi-structured interviews explored the consequences of COVID-19 on the health of RAS living in reception centres, the measures implemented to contrast the diffusion of the epidemic and the challenges that interviewees had in handling the emergency. After transcription, the interviews were analyzed using deductive and inductive approaches. Results: All key-informants agreed to participate in the study. Even though various measures were implemented in reception centres (i.e. mass quarantine, supply of personal protective equipment, risk communication campaigns and specific governance tools) they often had a discriminatory approach towards migrants and only considered the biomedical aspects of COVID-19, excluding its social roots and repercussions. This factor, together with the lack of an effective governance system at both the local and the national level, was the most relevant issue associated with the management of the syndemic in reception facilities and affected all the social determinants that shape the health profile of RAS. Conclusions: The study revealed the importance of social factors in the management of the syndemic in reception centres. It also highlighted how the underlying causes of the impact of COVID-19 are tightly correlated to the political and social approaches of local and national institutions to migration. In order to guarantee the well-being of society as a whole and successfully control the epidemic, it is necessary to consider migration as a human reality rather than an emergency, and demolish all the policies and bureaucratic systems that act as structural violence on RAS. This process brings into play different levels of responsibility and many action plans. We need to develop intersectoral collaborations for more holistic and interconnected practices, while investing the resources to build a worthy reception system and effective social protection programs. This way it will be possible to develop more inclusive approaches to public health and guarantee the conditions for RAS' empowerment.